Is It Time to Begin a Public Campaign Concerning Frailty and Pre-frailty? A Review Article - Sacha, Jerzy; Sacha, Magdalena; Soboń, Jacek; Borysiuk, Zbigniew; Feusette, Piotr (Frontiers in Physiology, 2017)
Frailty is a state that encompasses losses in physical, psychological or social domains. Therefore, frail people demonstrate a reduced potential to manage external stressors and to respond to life incidents. Consequently, such persons are prone to various adverse consequences such as falls, cognitive decline, infections, hospitalization, disability, institutionalization, and death. Pre-frailty is a condition predisposing and usually preceding the frailty state. Early detection of frailty (i.e., pre-frailty) may present an opportunity to introduce effective management to improve outcomes. Exercise training appears to be the basis of such management in addition to periodic monitoring of food intake and body weight. However, various nutritional supplements and other probable interventions, such as treatment with vitamin D or androgen, require further investigation. Notably, many societies are not conscious of frailty as a health problem. In fact, people generally do not realize that they can change this unfavorable trajectory to senility. As populations age, it is reasonable to begin treating frailty similarly to other population-affecting disorders (e.g., obesity, diabetes or cardiovascular diseases) and implement appropriate preventative measures. Social campaigns should inform societies about age-related frailty and pre-frailty and suggest appropriate lifestyles to avoid or delay these conditions. In this article, we review current information concerning therapeutic interventions in frailty and pre-frailty and discuss whether a greater public awareness of such conditions and some preventative and therapeutic measures may decrease their prevalence.